Copy number variation in Y chromosome multicopy genes is linked to a paternal parent-of-origin effect on CNS autoimmune disease in female offspring - Case, Laure K (Genome Biol, 2015)
BACKGROUND: The prevalence of some autoimmune diseases is greater in females compared with males, although disease severity is often greater in males. The reason for this sexual dimorphism is unknown, but it may reflect negative selection of Y chromosome-bearing sperm during spermatogenesis or male fetuses early in the course of conception/pregnancy. Previously, we showed that the sexual dimorphism in experimental autoimmune encephalomyelitis (EAE) is associated with copy number variation (CNV) in Y chromosome multicopy genes. Here, we test the hypothesis that CNV in Y chromosome multicopy genes influences the paternal parent-of-origin effect on EAE susceptibility in female mice. RESULTS: We show that C57BL/6 J consomic strains of mice possessing an identical X chromosome and CNV in Y chromosome multicopy genes exhibit sperm head abnormalities and female-biased sex ratio. This is consistent with X-Y intragenomic conflict arising from an imbalance in CNV between homologous X:Y chromosome multicopy genes. These males also display paternal transmission of EAE to female offspring and differential loading of microRNAs within the sperm nucleus. Furthermore, in humans, families of probands with multiple sclerosis similarly exhibit a female-biased sex ratio, whereas families of probands affected with non-sexually dimorphic autoimmune diseases exhibit unbiased sex ratios. CONCLUSIONS: These findings provide evidence for a mechanism at the level of the male gamete that contributes to the sexual dimorphism in EAE and paternal parent-of-origin effects in female mice, raising the possibility that a similar mechanism may contribute to the sexual dimorphism in multiple sclerosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-015-0591-7) contains supplementary material, which is available to authorized users.